2005
DOI: 10.1042/bc20040138
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of aquaporin 4 and H+/K+‐ATPase in the stomachs of peptide YY (PYY) transgenic mice

Abstract: Background information. The hormone PYY (peptide YY), synthesized by endocrine cells in the pancreas, ileum, colon and stomach has widespread inhibitory effects on gastrointestinal and pancreatic fluid secretion. Transgenic mice expressing a viral oncoprotein under the control of the PYY gene 5 -flanking region develop well-differentiated colonic endocrine tumours producing mainly PYY and enteroglucagon. In the present study, we investigated the expression of AQP4 (aquaporin 4) water channel and H + /K + -ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Since the application of proton pump inhibitors evoking acid suppression substantially increased the number of fundic AQP4-expressing parietal cells in the mouse, the involvement of aquaporin in gastric secretory processes (acid secretion) has been postulated (Matsuzaki et al 2010). This is in line with previous findings noting a higher expression level of AQP4 in the stomach (due to increased number of AQP4-positive parietal cells) of peptide YY transgenic mice (Carmosino et al 2005).…”
Section: Discussionsupporting
confidence: 81%
“…Since the application of proton pump inhibitors evoking acid suppression substantially increased the number of fundic AQP4-expressing parietal cells in the mouse, the involvement of aquaporin in gastric secretory processes (acid secretion) has been postulated (Matsuzaki et al 2010). This is in line with previous findings noting a higher expression level of AQP4 in the stomach (due to increased number of AQP4-positive parietal cells) of peptide YY transgenic mice (Carmosino et al 2005).…”
Section: Discussionsupporting
confidence: 81%
“…β-actin was used as a positive control in the study because of its stability and consistency throughout all tissue samples (Katz et al, 2012). Similar positive control was used in a previous study of aquaporin and H+/K+-ATPase expression in transgenic mice (Carmosino et al, 2005). This study also confirmed the results of Jaffar, et.…”
Section: Discussionsupporting
confidence: 78%
“…A specific primer with a pair nucleotide of PLCforward 5'-CATGTGAAACATATTTTTAAGGAAA-3' and PLCreverse 5'-ATCCCCAAATGTCACTCGGTCC-3' (Fujimoto et al, 2004) were used to amplify cDNA. β-actinforward 5'-GTTTGAGACCTTCAACACCC-3' and β-actin reverse 5'-CCAATGGTGATGACCTGGCC-3' as a control (Carmosino, 2005) served as a positive control in the amplification process. The mixture was then kept in the thermal cycler machine (Eppendorf, Germany) for denaturation process.…”
Section: Amplification Of Cdna Conventional Pcrmentioning
confidence: 99%
“…Parietal cells are scattered along the gastric gland. When they migrate from their generating region to the base region of gastric gland during their life span, they gradually lose acid secretory activity [1][2][3]. Accumulation of rabeprazole (PPI, its pKa is about 5.0) in weakly acidic region is greater than those of other PPIs such as omeprazole, lansoprazole and pantoprazole (pKa around 4.0).…”
Section: Introductionmentioning
confidence: 98%